The origin of instability in enclosed horizontally driven convection. (March 2016) - Tsai, Tzekih; Hussam, Wisam K.; Fouras, Andreas; Sheard, Gregory J.
Highlights: Instability in horizontal convection in enclosure with aspect ratio 0.16 considered. Instability is thermally driven (Rayleigh–Bénard type). Convective instability found as low as Rayleigh number Ra  = 1.23 × 10 7 . Transverse (longitudinal) instability dominant at lower (higher) Rayleigh number. Abstract: We demonstrate that instability in enclosed horizontally driven convection is due to a convective buoyancy-driven transverse-roll instability resembling the classical Rayleigh–Bénard convection in the thermal forcing boundary layer rather than a shear instability in the corresponding kinematic boundary layer. Instability growth is weakly sensitive to the local velocity profile, with velocity shear acting to select a transverse roll mode in preference to longitudinal rolls. The convectively unstable region grows from the hot end of the forcing boundary with increasing Rayleigh number two orders of magnitude lower than the natural onset of unstable horizontal convection. This analysis highlights the importance of the thermal boundary layer to the instability dynamics of horizontal convection, elucidating the path towards an understanding of turbulence and heat transport scaling in horizontal convection at oceanic Rayleigh numbers.